All Days 2007
DOI: 10.2118/107844-ms
|View full text |Cite
|
Sign up to set email alerts
|

Field Studies of Drilling and Completion Fluids to Minimize Damage and Enhance Gas Production in Unconventional Reservoirs

Abstract: Field data and lab data are presented for various fluids pumped in low perm shales, coalbed methane and tight sandstone reservoirs. Commonly used surfactants, alcohols as well as a microemulsion system (ME) are evaluated. Lab data is presented that illustrates the cleanup of injected fluids in tight gas cores. Damage mechanisms are shown to be phase trapping and high capillary pressures. The microemulsion additive results in lower pressures to displace injected fluids from low permeability core samples over co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Prior to the implementation, it is important to investigate the performance of fracturing fluid at reservoir conditions. The measurement of fundamental properties of the used foaming agent such as interfacial tension and contact angle that are the basis for reducing capillary pressure are also essential to perform [89,90]. Additionally, the adsorption of surfactant as a foaming agent is equally important to study in order to estimate the chemical loss in the reservoir during the recovery process.…”
Section: Foaming Agent and Water Recoverymentioning
confidence: 99%
See 3 more Smart Citations
“…Prior to the implementation, it is important to investigate the performance of fracturing fluid at reservoir conditions. The measurement of fundamental properties of the used foaming agent such as interfacial tension and contact angle that are the basis for reducing capillary pressure are also essential to perform [89,90]. Additionally, the adsorption of surfactant as a foaming agent is equally important to study in order to estimate the chemical loss in the reservoir during the recovery process.…”
Section: Foaming Agent and Water Recoverymentioning
confidence: 99%
“…Furthermore, it has been reported that several field pilot tests were conducted to check the performance of surfactant for fracturing applications. Most of the pilot tests were conducted in the Barnett and Marcellus shales utilizing conventional surfactants which include nonionic alcohol ethoxylate surfactants and amphoteric and cationic surfactants [89]. The water recovery using conventional surfactants has been reported to achieve approximately 60% (an average of 3 wells) [89].…”
Section: Foaming Agent and Water Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…Hydraulic fracturing technology is the most important stimulation treatment for developing unconventional hydrocarbons. Water-based fracturing fluid is the most commonly used fluid, such as guar gum fracturing fluid, slick-water fracturing fluid, clean fracturing fluid, and so on. , However, it is reported that usually only 5–50% of the injected fluid can be successfully returned to the ground. These retained fluids (or so-called filtration loss fluid, or invading fluid) often cause greater damage to the reservoir matrix permeability, such as water-sensitivity damage and water-locking damage. Water-sensitivity damage can be improved by adding clay stabilizer into the fracturing fluid, while well shut-ins after hydraulic fracturing and adding cleanup additives are effective for water-locking damage. The effectiveness of well shut-ins after fracturing depends on the reservoir physical properties.…”
Section: Introductionmentioning
confidence: 99%